Affordable energy efficient housing: The Proposed Tema Community 23, Greater Accra Region. - Agbomanyi, Freeman Kwame (2011)
A thesis submitted to the Department of Architecture, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Architecture.